2011
DOI: 10.1128/jcm.01902-10
|View full text |Cite
|
Sign up to set email alerts
|

Host Factors and Portal of Entry Outweigh Bacterial Determinants To Predict the Severity of Escherichia coli Bacteremia

Abstract: Escherichia coli ranks among the organisms most frequently isolated from cases of bacteremia. The relative contribution of the host and bacteria to E. coli bacteremia severity remains unknown. We conducted a prospective multicenter cohort study to identify host and bacterial factors associated with E. coli bacteremia severity. The primary endpoint was in-hospital death, up to 28 days after the first positive blood culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
143
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 52 publications
(64 reference statements)
19
143
3
1
Order By: Relevance
“…Comparison with the virulence factor database (https://cge.cbs .dtu.dk/services/VirulenceFinder/) and with the study of Lefort et al (13) showed that sat, iha, iss, sfa, irp2, fyuA, and iucC genes were harbored by both isolates. Sat is a secreted autotransporter toxin that alters the structural and functional components of intercellular junctions (14), iha is an iron-regulated gene homologue adhesin that augments adherence to uroepithelial cells (15), sfa codes for the S fimbrial adhesin (13), iss is a serum survival gene associated with a 20-fold increase in complement resistance (16), and irp2, fyuA, and iucC genes belong to the iron capture systems (13).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with the virulence factor database (https://cge.cbs .dtu.dk/services/VirulenceFinder/) and with the study of Lefort et al (13) showed that sat, iha, iss, sfa, irp2, fyuA, and iucC genes were harbored by both isolates. Sat is a secreted autotransporter toxin that alters the structural and functional components of intercellular junctions (14), iha is an iron-regulated gene homologue adhesin that augments adherence to uroepithelial cells (15), sfa codes for the S fimbrial adhesin (13), iss is a serum survival gene associated with a 20-fold increase in complement resistance (16), and irp2, fyuA, and iucC genes belong to the iron capture systems (13).…”
Section: Resultsmentioning
confidence: 99%
“…VAP B2 phylogroup isolates were further characterized by presence of 11 additional VF [20], PCR O-typing [23], and B2-subgrouping [24].…”
Section: E Coli Isolates [See Electronic Supplementary Materials (Esm)]mentioning
confidence: 99%
“…Multiplex PCR was used to detect genes encoding for seven frequently encountered extraintestinal VF, which belong to the main classes of VF (adhesin, toxin, and iron capture system) (see ESM Table 1) [20]. The VF score was defined as the number of VF present divided by the number of VF tested for each isolate.…”
Section: E Coli Isolates [See Electronic Supplementary Materials (Esm)]mentioning
confidence: 99%
“…Lefort et al 9 reported that host driven risk factors and mode of bacterial entry were more important determinants of severity of sepsis then VFs. This COLI-BAFI study examined more than 1000 episodes of bacteremia from 15 centers and correlated severity of these episodes with bacterial determinants.…”
mentioning
confidence: 99%